Response: [adding epoetin alfa to intense dose-dense adjuvant chemotherapy for breast cancer: randomized clinical trial] - Möbus, Volker; Jackisch, Christian; Schneeweiss, Andreas; Huober, Jens; Lück, Hans-Joachim; Du Bois, Andreas; Thomssen, Christoph; Kurbacher, Christian M.; Kuhn, Walther; Nitz, Ulrike A.; Runnebaum, Ingo B.; Hinke, Axel; et al. (Journal of the National Cancer Institute, 2014)
Irwin Gross and Michael Auerbach address questions related to oral vs intravenous iron substitution in cancer patients receiving erythropoiesis stimulating agen